2018
DOI: 10.1186/s12882-018-1185-x
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial remodeling after kidney transplantation: a case report

Abstract: BackgroundLupus nephritis (LN) is one of the most common manifestations of systemic lupus erythematosus (SLE) and is often the most serious organ complication and the cause of premature death of such a patient. Most of other organs and systems can be also affected. A typical complication is a cardiovascular involvement leading to the development of heart failure. According to current therapeutic standards, kidney transplantation is the treatment of choice in patients with renal failure in course of LN. On the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
1
0
2
Order By: Relevance
“…Ранее в исследовании М. Łukaszewski et al (2018) было показано, что у пациентов с ХБП С5 и сердечно-сосудистыми заболеваниями (ССЗ) существует повышенный риск смерти по сравнению с общей популяцией [3].…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Ранее в исследовании М. Łukaszewski et al (2018) было показано, что у пациентов с ХБП С5 и сердечно-сосудистыми заболеваниями (ССЗ) существует повышенный риск смерти по сравнению с общей популяцией [3].…”
Section: Introductionunclassified
“…По сравнению с гемодиализом (ГД), преимуществом ТП является нормализация ССС за счет ремоделирования миокарда с улучшением систолической функции. ТП положительно влияет на эластичность аорты, что снижает постнагрузку ЛЖ и, возможно, является одним из основных механизмов, поддерживающих обратное ремоделирование ЛЖ [3]. По данным T. Zapolski et al (2019) успешная ТП у больных с уремической кардиомиопатией инициирует процесс ремоделирования ЛП.…”
Section: Introductionunclassified
“…It has been shown that regression of kidney failure after the transplantation procedure improves cardiac function in patients with congestive cardiomyopathy and long period of dialysis [11]. An important benefit of the KTx is cardiovascular improvement due to myocardial remodeling with improved systolic heart function [12]. The KTx also positively affects the elasticity of the aorta, which reduces the left ventricle afterload and perhaps it is one of the basic mechanisms supporting reverse remodeling of the left ventricle [13].…”
Section: Introductionmentioning
confidence: 99%